Episiotomy: an informed consent proposal. (19th March 2021) - Malvasi, Antonio; Trojano, Giuseppe; Tinelli, Andrea; Marinelli, Enrico; Zaami, Simona
Abstract: Purpose: Since every obstetric surgical procedure requires gaining informed consent from patient, we have set out to evaluate whether such requirement also applies to episiotomy. Material and methods: To that end, we have conducted a thorough search of relevant scientific literature on multidisciplinary databases (Scopus, PubMed, PubMed, Central, Research Gate, Google Scholar) and articles that were published from 1989 to March 2019. The search keys used were: "episiotomy, " "informed consent, " "complications, " "malpractice." Results: The sources that we have ultimately drawn upon, whilst acknowledging the need for a targeted informed consent for episiotomy, do not deal with the specifics of what such consent should include, in terms of information provided and related aspects. Therefore, the authors have laid out an episiotomy-targeted consent form, drawing upon opinions and indications from scientific societies and institutions, in order to properly reflect and document the patient's acceptance or refusal of the procedure. Conclusions: Valid consent documentation may well prove instrumental in staving off or reducing complications, malpractice and liability, and in order to safeguard health care operators from obstetric malpractice allegations.